Großflächiges Road Pricing für Pkw. Zwischen Theorie und Wirklichkeit. Ein Diskussionsbeitrag. - Kriebernegg, Georg (Deutscher Verkehrs-Verlag, 2005)
Vom Lkw zum Pkw, von der Finanzierung zur Verkehrslenkung? Während bei Road Pricing im Straßengüterverkehr die Finanzierung der Straßeninfrastruktur im Vordergrund steht, gewinnt im Pkw-Verkehr die Verkehrslenkung immer mehr an Bedeutung. Allerdings stehen den optimistisch stimmenden theoretischen Überlegungen vielfältige Probleme der praxistauglichen Umsetzung entgegen. difu

The basic idea of demand management with road pricing is to increase the costs which are relevant for the individual's decision making process. Although this idea is well known both in academic discussion and policy debate, there are many problems when introducing road pricing schemes. For example, modelling long-term effects still lacks in theory and in practice. Additional, the necessity of interoperability between countries, different competences for different types of roads as well as enormous technical standards to cover the large amount of private vehicles are difficulties to be handled. Anyway, the most important issue concerns another topic: It is necessary to reach sufficient public acceptance for implementation of road pricing but simultaneously, individual acceptance has to be low in order to change people's behaviour. Henceforth, the bottom line for a successful implementation is to solve this "dilemma in acceptance". difu
Keywords: Verkehr; Individualverkehr; Öffentlicher Verkehr; Personenverkehr; Straßenverkehr; Personenkraftwagen; Verkehrspreis; Verhaltensweise; Akzeptanz; Verkehrsteilnehmer; Verkehrslenkung; Lenkungsinstrument; Road-Pricing; Straßenbenutzungsgebühr; Maut